Islamization of Knowledge with Special Reference to Political Science (American Journal of Islam and Society, 1985)
IntroductionThis paper discusses the crisis of thought prevailing in the Muslim worldtoday, and considers it a fundamental cause of the current degeneration,decadence and backwardness of the “Ummah.” Hopefully, it also highlightsthe role the International Institute of Islamic Thought will play in counteractingand ultimately overcoming the crisis.Such a theme inevitably brings the Islamic concept of knowledge to theforefront. First of all it must be decided whether such an investigation is merelyan intellectual extravanganza or whether there is actually a real issue thatdeserves investigating. No one possessing insight into the condition of theUmmah can fail to realize that there exists a crisis involving a number of issuesand complex dimensions. These issues are:1. The backwardness of the Ummah.2. The weakness of the Ummah.3. The intellectual stagnation of the Ummah.4. The absence of Ijtihad in the Ummah.5. The absence of cultural progress in the Ummah.6. The Ummah’s losing touch with the basic norms of Islamic civilization.All these issues indicate, in one way or the other, the intellectual crisisprevailing in the Muslim World. There is no doubt that this crisis is the causeand, at the same time, evidence of the decadence and impotence of the Ummah,and prevents it from anything significant to the culture and civilizationof the modern world. This incapability is futher exacerbated by the frequencyof political, economic and military crises ...